Unsaturated shear strength of a silty sand - Schnellmann, Reto (2013)
Series of single stage, consolidated drained direct shear tests under different net normal stresses and matric suctions were carried out to evaluate the unsaturated shear strength behavior of a silty sand. A back pressure shear box was used to measure and control pore-air and pore-water pressures. The experimental data show that matric suction increases shear strength of the soil significantly following a highly non-linear relationship. An increase in net normal stress results in a higher shear strength and the shearing behavior changes gradually from a peak shear strength followed by a strain-softening behavior to a strain-hardening behavior. A comparison between experimental shear strength measurements and predicted unsaturated shear strength values was made and the results are presented in the paper.